Retrospective analysis of the formation and development of advertising as a socio-cultural phenomenon in Spain - A. A. Agrba (Ибероамериканские тетради)
The article examines the main stages of formation and development of advertising in Spain. The relevance of the research is determined by the lack of study of Spanish advertising as a socio-cultural phenomenon, as well as the need for a comprehensive cultural analysis of its features. The obtained data can contribute to the study of national and cultural originality of the Spanish worldview, as well as serve as an incentive for further research in this area. The aim of the study is to conduct a retrospective analysis of advertising activities in Spain, taking into account historical and socio-cultural realities. The basic tasks are to understand the socio-cultural origins of advertising in Spain and to determine the stages of its development. The methodological basis of the study consists of works on the history and culture of Spain. The special literature on advertising, history, cultural studies, philosophy, as well as articles in periodicals and electronic Internet sources served as an information base for the study. A study of advertising as an integral cultural phenomenon associated with the values and traditions of the peoples studied by many researchers, in particular R. Barth, M. Foucault, U. Eco, P. Bourdieu, B. Malinowski, C. Lévi-Strauss, C. Taylor. Sharing their proposed ideas this article refers to the retrospective analysis of formation and development of advertising as a sociocultural phenomenon in Spain.